Clinical and X-ray characteristics of respiratory tuberculosis in those elderly - O. N. Deykina; A. V. Perfil’ev; V. Yu. Mishin; Yu. G. Grigor’ev (Туберкулез и болезни лёгких)
106 elderly and aged patients suffering from new respiratory tuberculosis were examined. In 43% of patients tuberculosis was detected during examination for some other disorders. Manifestations of tuberculosis were subclinical. X ray signs of new tuberculosis were found against the background of the treated primary tuberculosis, non-specific pulmonary diseases, engorgement in pulmonary blood circulation, age-related changes in the lung tissue. The tuberculous lesions were not extensive and as a rule unilateral.